Arthroscopic Repair of Anterosuperior Massive Rotator Cuff Tears: Does Repair Integrity Affect Outcomes?. (July 2017) - Kim, Sung-Jae; Choi, Yun-Rak; Jung, Min; Lee, Wonyong; Chun, Yong-Min
Background: The purpose of this study was to investigate clinical outcomes and structural integrity after arthroscopic repair of anterosuperior massive rotator cuff tears (RCTs) and to compare clinical outcomes between healed and retear groups. Hypothesis: The authors hypothesized that although both groups would exhibit improved clinical outcomes compared with their preoperative status, the healed group would have better clinical outcomes than the retear group, and in the retear group, the subscapularis retear subgroup would have inferior outcomes compared with the intact subscapularis repair subgroup. Study Design: Case-control study; Level of evidence, 3. Methods: This study included 73 of 90 eligible patients who underwent arthroscopic repair of an anterosuperior massive RCT. Functional outcomes after 2-year follow-up were assessed using the visual analog scale (VAS) pain score, subjective shoulder value (SSV), American Shoulder and Elbow Surgeons (ASES) score, University of California, Los Angeles (UCLA) shoulder score, and active range of motion. Patients were assigned to the healed group (group H, n = 34) or retear group (group R, n = 39) based on magnetic resonance arthrography results at 6 months postoperatively. Group R was composed of subgroup R1 (subscapularis retear) and subgroup R2 (intact subscapularis repair). Results: Retearing occurred in 53% of patients. At 2-year follow-up, group H exhibited better outcomes for all functional scores versus group R, respectively ( P < .001): VAS pain score (1.0 vs 2.1), SSV (90.2 vs 77.4), ASES score (90.8 vs 76.6), and UCLA shoulder score (31.0 vs 24.9). Within both groups, all scores improved significantly compared with preoperative values ( P < .001). At follow-up, group H had significantly better forward flexion ( P = .018) and internal rotation ( P = .002) than group R; within both groups, active range of motion improved in all planes compared with the preoperative condition ( P < .001). Subgroup R1 exhibited inferior outcomes versus subgroup R2, respectively: VAS pain score (2.6 vs 1.5; P = .012), ASES score (70.9 vs 83.6; P = .013), SSV (70.9 vs 85.4; P = .005), and UCLA shoulder score (22.0 vs 28.5; P = .001). Conclusion: After arthroscopic repair of anterosuperior massive RCTs, 53% of patients exhibited retearing. The healed group had better functional outcomes than the retear group. The subscapularis retear subgroup exhibited significantly inferior outcomes compared with the intact subscapularis repair subgroup.